Plant-derived natural products against hepatocellular carcinoma: chemical diversity, mechanisms of action, and organ-based classification - Nourhan Hisham Shady; Aliaa Gamal; Asmaa Emad Fekry; Amna Mahmoud Sayed; Zaki Ebrahim Afify; Ziad Abdellah Mohamed; Ingy M. Hashad; Mohammed I. Rushdi; Ahmed Zayed; Usama Ramadan Abdelmohsen (Natural Product Research, 2026)

Pomegranate peel extract nanoparticles enhance insulin production and antioxidant activity of diabetic rats - Hanan Yousri Ibrahim Al Sayed; Mostafa I. Abdelglil; Hanan Ramadan H. Mohamed; Ahmed Abdel Aziz Baiomy; Ayman Saber Mohamed (Tissue and Cell, 2026)

Physiological Influences of Silver and Copper Nanoparticles and Chlorogenic Acid on Quality and Vase Life of Carnation (Dianthus caryophyllus) - Iman M. El-Sayed; Khaled M.A. Ramadan; Rasha A.M. El-Ziat; Mohammed Hewidy; Hani S. Saudy (Journal of Soil Science and Plant Nutrition, 2026)

Biosynthesis of Magnetite Nanoparticles and its Impact on Productivity and Biochemical Components of Chili Pepper Under Saline Conditions - Mansour E. Ramadan; Mahmoud M. El-Saber; Ahmed E. Abdelhamid; Ahmed A. El-Sayed (Agricultural Research, 2026)

Drying kinetics, moisture diffusivity, and quality preservation of mint leaves using an IoT-assisted hybrid solar dryer with air recirculation - El-Sayed Gomaa Khater; Adel Hamed Bahnasawy; M. Alhumedi; Atef Fathy Ahmed; Ali Majrashi; Bassem N. Samra; Ramadan ElGamal; Abdallah Elshawadfy Elwakeel; Amged El-Harairy; Mohamed Hamdy Eid; Aml Abubakr Tantawy; Khaled A. Metwally (Journal of Stored Products Research, 2026)

Date seed–and licorice–derived nanoemulsions inhibit clinostomid metacercariae recovered from naturally infected Nile tilapia (Oreochromis niloticus): First report - Olfat A. Mahdy; Mai A. Salem; Fady Sayed Youssef; Mohamed S. Kamel; Reem M. Ramadan (Veterinary Parasitology, 2026)

The impact of Spirulina platensis supplementation on performance and immune response in laying hens - Mohammed Al-Rasheed; Mohamed Shawky El Sayed; Khaled M. A. Ramadan; Eslam S. A. Bendary; Sherief Mohmaed Abdel-Raheem (Veterinary Research Communications, 2026)

Ecological Risk Assessment and Environmental Status of Heavy Metals for the Bottom Sediments of Sharm El-Luli, Red Sea Coast, Egypt - Mohammed H. Aljahdali; Ramadan M. El-Kahawy; Mostafa M. Sayed; Petra Heinz; Michael Wagreich (Journal of Marine Science and Engineering, 2026)
Sharm El-Luli, one of the most pristine embayments along Egypt’s Red Sea coast, is increasingly recognized as a sensitive sink for terrigenous inputs and emerging anthropogenic pressures. This study assesses the distribution, sources, and ecological and human health implications of heavy metals in bottom sediments collected throughout the lagoon. Concentrations of Fe, Mn, Zn, Cu, Pb, Ni, Cd, and Co were quantified and assessed using a suite of geochemical indicators and environmentally based indices. Sediment quality guidelines (SQGs; TEL–PEL and ERL–ERM) were applied to evaluate potential biological effects. Most metals exhibited background to minor enrichment, although localized elevations of Pb, Ni, and Zn suggest contributions from episodic wadi runoff and limited tourism-related inputs. Igeo and CF values generally indicated low to moderate contamination, while SQG comparisons showed that exceedances of TEL values occurred primarily for Ni and Pb, implying occasional risk for benthic organisms. Multivariate statistical analysis (PCA) separated metals into two principal components: a lithogenic component dominated by Fe, Mn, and Co, reflecting the influence of Precambrian source rocks; and an anthropogenic-mixed component (Pb, Zn, Cu, Ni) associated with terrigenous pulses and local human activity. Human health risk assessment (non-carcinogenic) showed hazard index (HI) values below unity for both adults and children, indicating negligible immediate health concerns, while potential carcinogenic risk raised in adults via ingestion for Cr followed by Cd and Ni than in children. The results highlight that while Sharm El-Luli remains relatively unimpacted, the lagoon’s geomorphology and low hydrodynamic energy promote metal retention, underscoring the need for continuous monitoring as coastal use intensifies.

Efficacy and safety of lorundrostat in uncontrolled hypertension: a meta-analysis - Alaa Abdrabou Abouelmagd; Shrouk Ramadan; Mohamed Saad Sayed; Omar Abdulrahman Saad; Mazen Negmeldin Yassin; Alaa Mohammed Mostafa; Kerollos Abdelsayed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Lorundrostat, a novel selective aldosterone synthase inhibitor, has emerged as a potential treatment for uncontrolled hypertension. However, a comprehensive summary of its efficacy and safety profile is currently lacking. This meta-analysis aims to synthesize evidence from published randomized controlled trials (RCTs) to evaluate the clinical benefits and risks of lorundrostat in this patient population. Following the PRISMA guidelines, a systematic search was conducted on PubMed, Scopus, and Web of Science for RCTs comparing lorundrostat with placebo. The primary outcomes were changes from baseline in systolic and diastolic blood pressure. Data were pooled using a random-effects model to calculate mean differences (MD) for continuous outcomes and risk ratios (RR) for dichotomous outcomes, with corresponding 95% confidence intervals (CIs). Three RCTs comprising 1568 patients were included. Compared to placebo, lorundrostat significantly reduced both 24-h systolic blood pressure (MD: − 6.65 mmHg; 95% CI: [− 9.95 to − 3.35]) and office systolic blood pressure (MD: − 7.94 mmHg; 95% CI: [− 9.72 to − 6.15]). While the risk of serious adverse events was comparable, lorundrostat was associated with a higher incidence of hyperkalemia (RR: 5.47; 95% CI: [1.55 to 19.36]) and hyponatremia (RR: 1.95; 95% CI: [1.13 to 3.36]). Notably, lorundrostat significantly reduced the risk of adrenal insufficiency (RR: 0.15; 95% CI: [0.03 to 0.91]). Lorundrostat may be an effective agent for lowering blood pressure in patients with uncontrolled hypertension. Its safety profile is acceptable but requires careful monitoring of serum electrolytes and renal function. The reduced risk of adrenal insufficiency highlights its selectivity and potential as a valuable therapeutic option. Further large-scale, long-term studies are needed to confirm its sustained benefits and safety.

Geological characteristics and economic potential of paleozoic formations in the Um Bogma Area, Southwestern Sinai, Egypt - Fatma Ramadan; Sami K. Aita; Abd Elazeam Sayed; Ahmed G. Hassan; Abdulgafar K. Amuda; Mohamed Faisal (Euro-Mediterranean Journal for Environmental Integration, 2026)

Metabolomic and biofunctional insights into lemon-ginger mixture protection against heated oil hepatotoxicity - Nehal S. Ramadan; Ahmed Zayed; Magdy M. El-Sayed; Tarik A. Mohamed; Rasha S. Mohamed; Karem Fouda; Mohamed A. Farag (Food Research International, 2026)

Molecular mechanisms underlying cyclophosphamide-induced ovarian injury and protective strategies - Ehab E. Sharata; Taha Bakry; Habiba Gamal Atta; Habiba Atef Mohammed; Nazema Shaker Diab; Rofaida Ashraf Atef; Roaa Sayed Hosney; Mahmoud Mohamed Omar; Ramadan A. M. Hemeida (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Cyclophosphamide (CP) is an anti-cancer medication that also treats chronic inflammatory illnesses caused by the immune system. Although CP is widely used, it can occasionally have limited therapeutic efficacy due to its significant combined toxicities. Ovarian damage caused by CP is a major problem for patients, and premature ovarian failure (POF) is a serious side effect of CP that commonly affects female patients. Mechanistic investigations have implicated oxidative stress, inflammatory responses, and apoptosis as critical components in the etiology of CP-induced POF, although the exact process by which this ovarian toxicity occurs remains unclear. After CP causes ovarian cells to generate proinflammatory cytokines, including interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), nuclear factor kappa B (NF-κB) is activated. The activation of the NLRP3 inflammasome is the subsequent stage. In addition, Nrf2/HO-1 has been identified as an important signaling pathway that mitigates oxidative stress in CP-induced POF due to its anti-inflammatory and antioxidative characteristics. Moreover, several recent studies highlighted the role of α-klotho deficiency in ovarian aging. Quercetin, resveratrol, berberine, curcumin, irbesartan, mirtazapine, sildenafil, atorvastatin, donepezil, cilostazol, moxibustion, LCZ696, buspirone, levomilnacipran, melatonin, diosmin, and azilsartan are some of the agents that may protect against ovarian injury caused by CP, as shown in Graphical abstract. Our goal in writing this study is to provide a concise overview of the possible redox molecular pathways that cause ovarian harm in CP and how to potentially ameliorate them. Finally, investigation into these molecular pathways may pave the way for early ovarian damage relief and for the development of different agent strategies to alleviate CP-mediated POF. Graphical Abstract

The Gut–Brain Axis in Autism: Inflammatory Mechanisms, Molecular Insights, and Emerging Microbiome-Based Therapies - Helal F. Hetta; Fawaz E. Alanazi; Saleh F. Alqifari; Mostafa A. Sayed Ali; Mousa Aodh Albalwi; Ahmad Abdualrazag Albalawi; Yasmin N. Ramadan (Molecular Neurobiology, 2026)

Valorizing calcinated-bentonite in the production of hydrothermally cured geopolymers with high mechanical-efficacy - D.G. Sayed; M. Ramadan; Alaa Mohsen (Process Safety and Environmental Protection, 2025)

Comparative analysis of nutritional, rheological, and sensory attributes of biscuits enriched with white and black chia seed powders: Evaluation under Egyptian cultivation conditions - Clara R. Azzam; Sayed M. Mostafa; Mokhtar S. Rizk; Ramadan A. Arafa; Emad A. Salem; Ahmed M.S. Hussein (Innovative Food Science & Emerging Technologies, 2025)

Effect of pomegranate peel powder extract (ethanolic) on performance, egg quality, thyroid hormones, antioxidant parameters, interferon γ, lipid and protein profiles of aged laying hens - Ramadan Allam Sayed AbdElrasoul; Samah Mohamed Youssef; Randa Ahmed Deif-Allah; Marwa Hosni Abd El-Maged (Tropical Animal Health and Production, 2025)
Pomegranate peel extract is rich in total phenolics with high antioxidant activity. Furthermore, prolonging the laying period of hens is a growing trend that offers both financial and environmental benefits. Therefore, the current study aimed to investigate the potential effects of Pomegranate peel powder extract (PPPE) on aged laying chickens. One hundred twelve ISA White chickens, 80 weeks old, were randomly distributed into 4 groups, with seven replicates of 4 birds each. The first group received a basal diet (control group), which contains 170 mg of crude protein/kg diet with 2800 Kcal ME/kg of diet, while the second, third, and fourth groups received a basal diet supplemented with PPPE at levels of 100, 200, and 300 ppm, respectively. For daily egg mass (EM) per hen, egg production (EP%), feed conversion ratio (FCR), eggshell strength (kg/cm 2 ), Haugh unit, total protein (TP), and globulins (G) were significantly ( p < 0.001) improved by adding 100 ppm of PPPE in laying hens’ diets compared to other treatments. Furthermore, all hens receiving the experimental treatments had the best yolk color, yolk weight, yolk/albumin ratio, shell weight of egg, plasma total cholesterol (Cholest), low-density lipoprotein, T3, and T3/T4 ratio. The shell thickness was recorded as the highest value in birds receiving 200 ppm. Furthermore, laying hens fed a diet supplemented with PPPE100 recorded the highest total antioxidant capacity (TAOC) and phosphorus levels of plasma and the lowest interferon γ (INF-γ) and plasma calcium levels. In conclusion, supplementing PPPE at 100 ppm to the basal diet improved aged laying hens’ performance, quality and strength of eggs, TAOC, (INF-γ), Cholest, LDL, and liver function. In addition, more studies are required to investigate PPPE in laying chickens, especially in the last production phase.

Balancing efficacy and hepatotoxicity: a comprehensive review of oral medications in psoriasis management - Alaa E. Elsisi; Sally El-Sayed Abu-Risha; Mahmoud Abdelrahman Alkabbani; Laila A. Ramadan; Samia Salem Sokar (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Psoriasis is a chronic, immune-mediated inflammatory disorder that significantly impacts patients’ quality of life. Oral systemic therapies, including methotrexate, cyclosporine, acitretin, and apremilast, remain integral to psoriasis management, particularly for patients with moderate-to-severe disease who cannot afford biologic therapy. While these treatments are effective, their long-term use is often limited by adverse effects, particularly hepatotoxicity. Methotrexate and acitretin are associated with liver toxicity, requiring regular monitoring, whereas cyclosporine presents a lower but notable risk. Apremilast, a phosphodiesterase 4 inhibitor, offers a safer hepatic profile but has lower efficacy than traditional systemic agents. Emerging therapies, such as TYK2 inhibitors, RORγt inhibitors, and novel PDE4 inhibitors, aim to improve treatment efficacy while minimizing adverse effects. Advances in understanding hepatotoxicity mechanisms have led to identifying predictive biomarkers and hepatoprotective strategies, including antioxidants and non-invasive imaging techniques. Personalized medicine approaches, including pharmacogenomics, are revolutionizing treatment selection by optimizing efficacy while minimizing toxicity risks. This comprehensive review examines oral psoriasis treatments’ efficacy and hepatotoxicity profiles, discusses novel therapeutic developments, and explores strategies for mitigating liver-related adverse effects. A balanced approach that integrates clinical monitoring, lifestyle modifications, and emerging precision medicine techniques is essential for optimizing long-term treatment outcomes. Future research should focus on refining predictive models for drug-induced liver injury and developing targeted therapies with improved efficacy and safety profiles. Graphical Abstract Created in BioRender. Elgindy, A. (2025) https://BioRender.com/vcab653

Acaricidal activity of Astragalus polysaccharides nanoemulsion against camel tick, Hyalomma dromedarii - Shimaa Abdel-Radi; Mai A. Salem; Fady Sayed Youssef; Mohamed S. Kamel; Mohamed M. El-Bahy; Reem M. Ramadan (Experimental and Applied Acarology, 2025)
Hyalomma dromedarii ( H. dromedarii ) is a major ectoparasite of camels in arid regions such as Egypt, where it causes significant economic losses and transmits several zoonotic pathogens. This study evaluated the acaricidal efficacy of a novel, locally prepared Astragalus polysaccharides nanoemulsified formulation (APS-NE) against various developmental stages of H. dromedarii infesting camels. APS-NE was prepared using ultrasonic emulsification and characterized by dynamic light scattering, transmission electron microscopy, and GC–MS, revealing uniform nanoparticle size (30–53 nm), good water solubility, and bioactive constituents including palmitic acid and quercetin derivatives. The formulation exhibited strong biological activity with very low toxicity and a wide safety margin in mice. In vitro bioassays showed a clear concentration-dependent acaricidal effect following short immersion periods: at 2% APS-NE, mortality reached 100% for eggs, larvae, nymphs, and unfed adults. Mortality rates at lower concentrations (0.5–1.5%) ranged from 63.6% to 94.6% in eggs, 33.6% to 84.3% in larvae, 53.3% to 93.6% in nymphs, and 31% to 87% in unfed adults, with larvae being the most susceptible stage. APS-NE also significantly impaired reproductive parameters in engorged females, including reductions in egg production index, egg mass, and hatchability compared to the reference drug. Strong positive correlations were observed between APS-NE concentration and tick mortality, with negative correlations for reproductive metrics. These results highlight APS-NE as a safe, eco-friendly alternative to conventional acaricides for effective H. dromedarii control, supporting integrated tick management strategies.

Reprogramming the hepatic immune microenvironment with mirtazapine in early neoplastic transformation: Evidence from a diethylnitrosamine-induced rat model - Elsayed A. Elmorsy; Sameh Saber; Ahmad H. Alhowail; Abousree T. Ellethy; Enas A. Mohamed; Hamad Alsaykhan; Hatim Y. Alharbi; Omar Almansour; Abdelrahman El-Sayed; Manal Mohamed Hatem; Ahmed Kaid Alantry; Walaa A. Allam; et al. (Chemico-Biological Interactions, 2025)

First report of Astragalus polysaccharide nanoemulsion efficacy against Clinostomid metacercariae in Nile Tilapia - Mai A. Salem; Olfat A. Mahdy; Fady Sayed Youssef; Mohamed S. Kamel; Reem M. Ramadan (Veterinary Parasitology, 2025)

Benthic Ostracods as Indicators of Nearshore Pollution: An Example from Hurghada Bay, Red Sea Coast, Egypt - Ramadan M. El-Kahawy; Petra Heinz; Mostafa M. Sayed; Ammar Mannaa; Rabea A. Haredy; Michael Wagreich (Journal of Marine Science and Engineering, 2025)
Twenty-nine sediment samples were collected from Hurghada Bay, a highly impacted coastal area along the Northern Red Sea of Egypt, to evaluate environmental quality and human-induced effects on benthic ostracods. As potential bioindicators, benthic ostracods are highly responsive to environmental disturbances, with pollution leading to reduced abundance, lower diversity, and increased opportunistic taxa. To investigate the link between ostracod assemblages and sediment contamination, we measured the concentrations of eight heavy metals (Cu, Cd, Zn, Pb, As, Cr, Ni, and Mn) using inductively coupled plasma–atomic emission spectrometry (ICP-AES). Multivariate statistical analyses identified three distinct ostracod assemblages distributed across three station groups with varying pollution levels. Group I, associated with offshore stations, exhibited low to moderate heavy metal (HM) concentrations and high ostracod abundance and was dominated by Moosella striata, Hiltermannicythere rubrimaris, Ruggieria danielopoli, Neonesidea schulzi, and Paranesidea fracticorallcola, where the water depth and sand content are the main controlling factors. In contrast, Group II, corresponding to stations with the highest HMs and total organic matter (TOM), was dominated by pollution-tolerant species Jugosocythereis borchersi, Cyprideis torosa, Alocopocythere reticulata, and, to a lesser extent, Ghardaglaia triebeli, with reduced ostracod density and diversity. Group III, characterized by stations influenced by the mud-controlling factor, had the lowest HMs and was dominated by pollution-sensitive species Xestoleberis rhomboidei, Paranesidea fortificata, and Loxocorniculum ghardaquensis. These findings highlight the ecological risks posed by HM pollution and emphasize the urgent need for pollution mitigation strategies and continued monitoring to preserve the Red Sea’s benthic biodiversity.

Overcoming challenges in the analysis of the ubiquitous emerging contaminant trifluoroacetic acid employing trap column liquid chromatography tandem mass spectrometry - Ramadan Sayed; Ahmed A. Omran; Rabie S. Farag; Hend A. Mahmoud; Mostafa Soliman (Journal of Hazardous Materials, 2025)

Whole genome sequencing identifies monogenic disease in 56.1% of families with early-onset steroid-resistant nephrotic syndrome - Neveen A. Soliman; Mohamed A. Elmonem; Ahmed F. El-Sayed; Eman Ramadan; Ahmed M. Badr; Fatma M. Atia; Rasha Helmy; May O. Amer; Ahmed Abd El-Raouf; Fadya M. El-Garhy; Omnia M. Abdel-Haseb; Tokka M. Hassan; et al. (Human Genetics, 2025)
Genetic causes of steroid-resistant-nephrotic-syndrome (SRNS) represent a rapidly growing number of monogenic diseases. The reported diagnostic yield of various studies applying genetic panels and exome-sequencing to diagnose SRNS is usually < 30%. We performed genome-sequencing in a cohort of Egyptian SRNS patients. We recruited 47 SRNS patients belonging to 41 unrelated families [28 males/19 females; median (range): 6 (0.5–22 years)]. We established a pipeline for genome sequencing, bioinformatics analysis, variant curation and protein modeling at the Egypt Center for Research and Regenerative Medicine (ECRRM). Disease-causing variants were detected in 27/47 patients (57.4%) belonging to 23/41 families (56.1%), including nine novel variants in NPHS1, NPHS2, COL4A3, MYO1E, NUP93, PLCE1, PODXL, SMARCAL1 and WT1 . Novel variants were confirmed by Sanger sequencing and were segregated in families of affected patients. NPHS2 was the most common causative gene in 8/23 (34.8%) of confirmed families, followed by NPHS1 , WT1 , and SMARCAL1 in 2/23 families (8.7%) each. All detected missense variants were evaluated through protein modeling and were predicted deleterious. Our study expanded the spectrum of SRNS disease-causing variants and revealed a monogenic cause in 56.1% of investigated families. In our cohort, no deep intronic or regulatory variants were detected by genome-sequencing. Pursuing genetic diagnosis in SRNS patients is crucial to inform clinical decision making, genetic counseling, transplantation strategy and prenatal diagnosis thus improving clinical outcome of affected patients.

Smart application of silver nanoparticles in the treatment of chicken coccidiosis in combination with special supplement to alleviate its toxicity - Marwa M. Khalifa; Hend I. Mohamed; Reem M. Ramadan; Fady Sayed Youssef; Mohamed M. El-Bahy; Shimaa Abdel-Radi (Veterinary Parasitology, 2025)

Paleobiodiversity, Paleobiogeography, and Paleoenvironments of the Middle–Upper Eocene Benthic Foraminifera in the Fayum Area, Western Desert, Egypt - Mostafa M. Sayed; Petra Heinz; Ibrahim M. Abd El-Gaied; Ramadan M. El-Kahawy; Dina M. Sayed; Yasser F. Salama; Mansour H. Al-Hashim; Michael Wagreich (Journal of Marine Science and Engineering, 2025)
The middle–upper Eocene successions of northwest Fayum, Egypt, provide a crucial archive for reconstructing paleoenvironmental conditions and paleobiogeographical patterns of the southern Tethys realm. Stratigraphically, the investigated section is subdivided into three rock units: the Gehannam Formation (Bartonian-Priabonian), the Birket Qarun Formation, and the Qasr El Sagha Formation (Priabonian). A total of 101 benthic foraminiferal taxa, representing 31 genera, 23 families, 13 superfamilies, and four suborders, were identified. The middle–late Eocene age is primarily determined by the co-occurrence of index spinose planktonic foraminifera (Acarinina spp., Morozovelloides spp., and Globigerinatheka semiinvoluta) and benthic foraminiferal assemblages, further supported by the presence of the nannofossil marker Chiasmolithus oamaruensis. Four local benthic biozones are identified and correlated with coeval zones in nearby areas. Quantitative analyses of benthic foraminiferal individuals, diversity indices, ecological parameters, and the benthic foraminiferal oxygen index (BFOI) reveal distinct environmental shifts. The rock unit occupied by the late middle Eocene assemblages is diversified and dominated by calcareous infaunal taxa (e.g., Bolivina spp., Fursenkoina spp., and Nonionella spp.), indicative of low-oxygen outer neritic conditions associated with elevated organic influx. In contrast, the late Eocene Birket Qarun and Qasr El Sagha showed an increase in epifaunal forms and reduced diversity, suggesting a transition to dysoxic-oxic conditions. Paleobiogeographical analysis indicates a strong affinity with the Tethyan realm, with potential faunal exchange through the Trans-Saharan Seaway. These findings enhance our understanding of Paleogene marine connections between the Tethyan and Indo-Pacific realms, contributing to broader discussions on Eocene paleobiogeography and depositional dynamics in North Africa.

Herbal remedies for oral and dental health: a comprehensive review of their multifaceted mechanisms including antimicrobial, anti-inflammatory, and antioxidant pathways - Mohamed A. Anwar; Ghadir A. Sayed; Dina M. Hal; Mohamed S. Abd El Hafeez; Abdel-Aziz S. Shatat; Aya Salman; Nehal M. Eisa; Asmaa Ramadan; Riham A. El-Shiekh; Shymaa Hatem; Shaza H. Aly (Inflammopharmacology, 2025)
Across diverse cultures, herbal remedies have been used to alleviate oral discomfort and maintain dental hygiene. This review presents studies on herbal remedies with remarkable antimicrobial, anti-inflammatory, antioxidant, anticancer, anticaries, analgesic, and healing properties. The manuscripts demonstrate the depth of scientific inquiry into herbal remedies used for the management of various oral and dental health conditions. These include gingivitis, oral ulcers, mucositis, periodontitis, oral pathogens, carcinoma, xerostomia, and dental caries. Researchers have investigated the phytochemical and pharmacological properties of plant-derived compounds and their extracts evaluated their interactions with oral pathogens and inflammatory processes. The convergence of traditional knowledge and rigorous scientific investigation offers a compelling narrative, fostering a deeper understanding of herbal remedies as viable alternatives to conventional dental interventions. This work has the potential to provide patients with access to gentle, yet effective solutions, and simultaneously offer dental health professionals the opportunity to enrich their knowledge, and ability to provide personalized, holistic care. This review highlights the symbiotic relationship between herbal medicine and scientific understanding, emphasizing the importance of disseminating this knowledge to benefit both practitioners and patients, enabling evidence-based decision-making in dental care. The exploration of herbal remedies offers a promising alternative, potentially mitigating some of these side effects while promoting oral health in a more natural and holistic manner.

Cordia dichotoma G. Forst fruit prophylactic against Alzheimer's risk factors: in vitro study - Faten Mohamed Ibrahim; Abeer Yousry Ibrahim; Heba Mostafa Amer; Mohamed Fawzy Ramadan; Reda Sayed Mohammed (Rendiconti Lincei. Scienze Fisiche e Naturali, 2024)

Effects of mesenchymal stem cells versus curcumin on sonic hedgehog signaling in experimental model of Hepatocellular Carcinoma - Marwa Sayed Abdel-Tawab; Hanan Fouad; Ahmed Yahia Sedeak; Noha A. Doudar; Enas Ezzat Rateb; Eman Faruk; Hoda Ramadan Reyad (Molecular Biology Reports, 2024)

Correction: Circulating hsa-miR-221 as a possible diagnostic and prognostic biomarker of diabetic nephropathy - Marwa Sayed Abdel-Tawab; Mohamed Gamal Mohamed; Noha A. Doudar; Enas Ezzat Rateb; Hoda Ramadan Reyad; Naglaa Adli Abd Elazeem (Molecular Biology Reports, 2024)

Retraction Note: The Protective Role of Toll-Like Receptor Agonist Monophosphoryl Lipid A against Vaccinated Murine Schistosomiasis - Ibrahim Aly; Essam H. Ibrahim; Rabab S. Hamad; Hoda E. L. Sayed; Sama M. N. Attiyah; Wafaa E-Komy; Hamed A. Ghramh; Ali Alshehri; Khalid M. Alsyaad; Mohammed Alshehri; Mona Kilany; Kareem Morsy; et al. (Acta Parasitologica, 2024)

Kiwi (Actinidia deliciosa) juice as a natural inhibitor of the enzymatic activity of sugarcane juice, insights from experimental assessment and molecular docking analysis - Heba Sayed Mostafa; Fatma Fakher Ramadan; Hagar Ahmad Emam; Engy Raafat Shaker; Wafaa Mostafa El Kady; Aya Khaled Sayed (Food Chemistry, 2024)

Towards the preparation of sustainable superplasticizers for geopolymeric pastes via radiation-induced grafting of sulfonic group-bearing monomers onto corn starch - Noha M. Deghiedy; Safaa M.A. El-Gamal; Mohamed Ramadan; Alaa Mohsen; Mahmoud M. Hazem; Mostafa A. Sayed; Fatma M. Helmy; Mona M. Wetwet; Ahmed E. Swilem (Carbohydrate Polymers, 2024)

Alleviation of irrigation water salinity impact on the growth and yield of sweet potato by plant growth-promoting rhizobacteria inoculation - Mansour El-Sayed Ramadan (Horticulture, Environment, and Biotechnology, 2024)

Developing green slag/bentonite-based geopolymers modified with meso-porous tungsten oxide: Zeolitic phases, mechanical performance and gamma-radiation mitigation - M. Ramadan; S.M.A. El-Gamal; Mona M. Wetwet; Mostafa A. Sayed; M.M. Hazem; Noha M. Deghiedy; Ahmed E. Swilem; Alaa Mohsen (Applied Clay Science, 2024)

Mycorrhizal colonization and calcium spraying modulate physiological and antioxidant responses to improve pepper growth and yield under salinity stress - Osama Abdelsalam Shalaby; Mansour El-Sayed Ramadan (Rhizosphere, 2024)

Circulating hsa-miR-221 as a possible diagnostic and prognostic biomarker of diabetic nephropathy - Marwa Sayed Abdel-Tawab; Mohamed Gamal Mohamed; Noha A. Doudar; Enas Ezzat Rateb; Hoda Ramadan Reyad; Naglaa Adli Abd Elazeem (Molecular Biology Reports, 2023)
Background Diabetic nephropathy (DN), which is a chronic outcome of diabetes mellitus (DM), usually progresses to end-stage renal disease (ESRD). The DN pathophysiology, nevertheless, is not well-defined. Several miRNAs were reported to be either risk or protective factors in DN. Methods, and results The present study sought to inspect the potential diagnostic and prognostic value of hsa-miR-221 in DN. The study included 200 participants divided into four groups: Group 1 (50 patients with DN), Group 2 (50 diabetic patients without nephropathy), Group 3 (50 nondiabetic patients with CKD), and Group 4 (50 healthy subjects as a control group). Patients in groups 1 and 3 were further classified based on the presence of macroalbuminuria and microalbuminuria. Hsa-miR-221 expression was measured by RT- qRT-PCR. DN patients had significantly elevated serum hsa-miR-221 levels than the other groups, while diabetic patients without nephropathy exhibited elevated levels compared to both nondiabetic patients with CKD, and the control group. The DN patients with macroalbuminuria revealed significantly higher mean values of hsa-miR-221 relative to the patients with microalbuminuria. Significant positive associations were observed in the DN group between serum hsa-miR-221 and fasting insulin, fasting glucose, HOMA IR, ACR, and BMI. The ROC curve analysis of serum hsa-miR-221 in the initial diagnosis of DN in DM revealed high specificity and sensitivity. Conclusions It is concluded that hsa-miR-221 has the potential to be a useful biomarker for prognostic and diagnostic purposes in DN.

Averrhoa carambola L. fruit and stem metabolites profiling and immunostimulatory action mechanisms against cyclosporine induced toxic effects in rat model as analyzed using UHPLC/MS-MS-based chemometrics and bioassays - Nehal S. Ramadan; Nesrin M. Fayek; Magdy M. El-Sayed; Rasha S. Mohamed; Ludger A. Wessjohann; Mohamed A. Farag (Food and Chemical Toxicology, 2023)

Synergistic effects of graphene oxide grafted with barbituric acid nanocomposite for removal of heavy metals from aqueous solution - Mostafa M. Abdel Wahab; Galal H. Sayed; Ramadan M. Ramadan; Amr H. Mady; Abdelrahman M. Rabie; Ahmed A. Farag; Nabel A. Negm; Eslam A. Mohamed (Nanotechnology for Environmental Engineering, 2023)

Enhanced adsorption performance of magnetic Ni0.5Zn0.5Fe2O4/Zn0.95Co0.05O nanocomposites for the removal of malachite green dye - Amani Aridi; Hadi Basma; Warde Chehade; Roudaina Sayed Hassan; Nader Yaacoub; Daoud Naoufal; Ramadan Awad (Environmental Science and Pollution Research, 2023)

Characterization of ZnO and Mn-doped ZnO nanoparticles and their antimicrobial activity - Yasser Fathy Abdelaliem; Tarob Abdel-Naby Abdel-Baset; Alaa Ropy Mahmoud Sayed; Aya Ahmed Owis; Mohamed Fawzy Ramadan; Adel Abdelrazek Abdelazim Mohdaly (Rendiconti Lincei. Scienze Fisiche e Naturali, 2023)

Morphometry, migration rates, and environmental hazards of barchan dunes in the Kharga Depression, Western Desert, Egypt - Mohamed Abdel Wahed; Mohamed A. Hamdan; Sayed Ramadan; Mai F. Gebril; Ahmed M. Abu Khadrah (Arabian Journal of Geosciences, 2023)
Barchan dunes of the Kharga Depression, Western Desert, Egypt, have been assessed in terms of their morphometry, grain size, and migration rate using remote sensing and GIS techniques and field and laboratory work. Thirty-seven sites were chosen along the Kharga dune belt and subdivided into northern, central, and southern sectors. At each site, several barchans were subjected to morphometric measurements (length, width, height, length of eastern and western horns, and length of windward and leeward sides). The rate and direction of 160 barchans were also measured for the period between 2002 and 2018. Grain size analysis was carried out on sand samples taken from the crest of these dunes. Statistically, significant relationships have been found between the morphometric parameters, dune migration, and grain size attributes. The analysis of the morphology of the barchan dunes, their movement, and the nature of sedimentary materials provide essential information for assessing and evaluating their environmental hazards.

The provenance and history of Abu Muharak barchan sands (Kharga Depression) inferred from textural, mineralogical, and geochemical perspectives - Sayed Ramadan; Mohamed A. Hamdan; Ahmed M. Abu Khadra; Mohamed Abdel Wahed (Arabian Journal of Geosciences, 2022)
The current study deals with textural, mineralogical, and geochemical characteristics of the barchan dune sands of Abu Muharak dune belts in the Kharga Depression. Abu Muharak is the longest dune belt in the Western Desert of Egypt. Sand samples from 37 sites were texturally, petrologically, and chemically analyzed. Our goals were to interpret the provenance of the sands in terms of grain size, petrology, and geochemistry and correlate these data with the proposed source such as Nubian sandstone, Pleistocene alluvial, and Holocene lacustrine sediments as well as ancient aeolian deposits exposed at the Kharga Depression. The present study concludes that the Moghra sandstone is the main source of the Abu Muharak dune belt with local contributions from Pleistocene alluvial and dune deposits as well as weathered Nubian sandstone in the Kharga Depression.

Potential of ( Citrus nobilis Lour × Citrus deliciosa Tenora) metabolites on COVID-19 virus main protease supported by in silico analysis - Seham S. El-Hawary; Marwa Y. Issa; Hanaa S. Ebrahim; Anber F. Mohammed; Alaa M. Hayallah; Essam M. Abd El-Kadder; Ahmed. M. Sayed; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

Metabolomic profiling and antioxidant potential of three fungal endophytes derived from Artemisia annua and Medicago sativa - Ahmed M. Sayed; Noheir H. Sherif; Ahmed O. El-Gendy; Yara I. Shamikh; Asmaa T. Ali; Eman Zekry Attia; Mo'men H. El-Katatny; Basma Ali Khalifa; Hossam M. Hassan; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

Cytotoxic potential of three Sabal species grown in Egypt: a metabolomic and docking-based study - Seham S. El-Hawwary; Fatema R. Saber; Hanan M. Abd Almaksoud; Hanan Elimam; Ahmed M. Sayed; Usama Ramadan Abdelmohsen (Natural Product Research, 2022)

The combined effect of water deficit stress and TiO2 nanoparticles on cell membrane and antioxidant enzymes in Helianthus annuus L. - Taha Ramadan; Suzan A. Sayed; Amna K. A. Abd-Elaal; Ahmed Amro (Physiology and Molecular Biology of Plants, 2022)
Nanotechnology has become one of the several approaches attempting to ameliorate the severe effect of drought on plant's production and to increase the plants tolerance against water deficit for the water economy. In this research, the effect of foliar application of TiO 2 , nanoparticles or ordinary TiO 2 , on Helianthus annuus subjected to different levels of water deficit was studied. Cell membrane injury increased by increasing the level of water deficit and TiO 2 concentration, and both types of TiO 2 affected the leaves in analogous manner. Ord-TiO 2 increased H 2 O 2 generation by 67–240% and lipid peroxidation by 4–67% in leaves. These increases were more than that induced by Nano-TiO 2 and the effect was concentration dependent. Proline significantly increased in leaves by water deficit stress, reaching at 25% field capacity (FC) to more than fivefold compared to that in plants grown on full FC. Spraying plants with water significantly decreased the activities of enzymes in the water deficit stressed roots. The water deficit stress exerted the highest magnitude of effect on the changes of cell membrane injury, MDA, proline content, and activities of CAT and GPX. Nano-TiO 2 was having the highest effect on contents of H 2 O 2 and GPX activity. In roots, the level of water deficit causes highest effect on enzyme activities, but TiO 2 influenced more on the changes of MDA and H 2 O 2 contents. GPX activity increased by 283% in leaves of plants treated with 50 and 150 ppm Nano-TiO 2 , while increased by 170% in those treated with Ord-TiO 2 , but APX and CAT activities increased by 17–197%, in average, with Ord-TiO 2 . This study concluded that Nano-TiO 2 didn’t ameliorate the effects of drought stress on H. annuus but additively increased the stress, so its use in nano-phytotechnology mustn’t be expanded without extensive studies.

Hepatoprotective effects of phytochemicals berberine and umbelliferone against methotrexate-induced hepatic intoxication: experimental studies and in silico evidence - Abdel-Gawad S. Shalkami; Emad H. M. Hassanein; Ahmed M. Sayed; Wafaa R. Mohamed; Marwa M. Khalaf; Ramadan A. M. Hemeida (Environmental Science and Pollution Research, 2021)

Evaluation of heavy metals accumulation risks in water of the Qalubiya drain in East Delta, Egypt - Fatma Ramadan; Hamdy El Sayed Nour; Sami Aita; Hadeer Raffat Zahran (Arabian Journal of Geosciences, 2021)

Assessment of sediment quality of the Qalubiya drain and adjoining soils, Eastern Nile Delta, Egypt - Hamdy El Sayed Nour; Fatma Ramadan; Sami Aita; Hadeer Zahran (Arabian Journal of Geosciences, 2021)

The Protective Role of Toll-Like Receptor Agonist Monophosphoryl Lipid A Against Vaccinated Murine Schistosomiasis - Ibrahim Aly; Essam H. Ibrahim; Rabab S. Hamad; Hoda E. L. Sayed; Sama M. N. Attiyah; Wafaa E-Komy; Hamed A. Ghramh; Ali Alshehri; Khalid M. Alsyaad; Mohammed Alshehri; Mona Kilany; Kareem Morsy; et al. (Acta Parasitologica, 2020)

Synthesis and antiviral activity of some pyrrolonyl substituted heterocycles as additives to enhance inactivated Newcastle disease vaccine - Alaa R. I. Morsy; Sayed K. Ramadan; Mounir M. Elsafty (Medicinal Chemistry Research, 2020)

Trichosporon jirovecii infection of red swamp crayfish ( Procambarus clarkii ) - Ebtsam Sayed Hassan Abdallah; Mahmoud Mostafa Mahmoud; Ismail Ramadan Abdel‐Rahim (Journal of Fish Diseases, 2018)
One hundred and twenty‐nine isolates of Trichosporon jirovecii were isolated from the melanized exoskeleton as well as eyestalks, gills, muscle and haemolymph of red swamp crayfish ( Procambarus clarkii ) collected from the River Nile, during summer 2015. Isolates were similar morphologically, biochemically and genetically. Also, random amplified polymorphic DNA (RAPD) analysis exhibited no polymorphism among the tested isolates. Virulence factors such as chitinase, protease, lipase activities and biofilm formation were examined. Challenge test, using a representative isolate (Tj_ASU8), proved its pathogenicity against crayfish. Magnesium oxide nanoparticles had a good antifungal activity with a minimum fungicidal concentration of 8 mg/ml. To the best of our knowledge, this is the first report for isolation of T. jirovecii from red swamp crayfish, showing melanization, from the River Nile. We assume that infected crayfish may act as a vector for this fungus and can disseminate infection to all susceptible hosts in the vicinity.

Aberrant Expression of Some Circulating miRNAs in Childhood Acute Lymphoblastic Leukemia - Menha Swellam; Maha Hashim; Magda Sayed Mahmoud; Amal Ramadan; Naglaa M. Hassan (Biochemical Genetics, 2018)

Propolis alleviates concanavalin A-induced hepatitis by modulating cytokine secretion and inhibition of reactive oxygen species - Fatma Mounieb; Laila Ramadan; El-Sayed Akool; Amany Balah (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Exploration of copper deposits in Wadi El Regeita area, Southern Sinai, Egypt, with contribution of remote sensing and geophysical data - S. M. Salem; Sultan Awad Arafa; T. M. Ramadan; El Sayed A. El Gammal (Arabian Journal of Geosciences, 2013)

Bioactive lipids and antioxidant properties of wild Egyptian Pulicaria incise, Diplotaxis harra, and Avicennia marina - M. F. Ramadan; M. M. A. Amer; H. T. Mansour; K. M. Wahdan; R. M. El-Sayed; S. El-Sanhoty; W. A. El-Gleel (Journal of Consumer Protection and Food Safety, 2009)